Non-Performing Financing and Efficiency as Predictive Factors for Profitability of Islamic Commercial Banks during the COVID-19 Pandemic - Rahman, Holilur; Aulia, Fena Ulfa; Fadilah, Fadilah (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this study was to examine the impact of NPF and the efficiency level of Islamic banks on the profitability of Islamic commercial banks during the pandemic.This study uses a quantitative approach with the type of explanatory research. The data analysis method used in this study is multiple linear regression analysis, the variables used in this study are variable X and variable Y, which includes variable X (independent variable) namely Non Performing Financing (X1) and Efficiency (X2). Variable Y (dependent variable) is Profitability.The results show that: First, partially Non-Performing Financing has an impact on the ROE of Islamic commercial banks, but the efficiency level of Islamic banks does not have an impact on ROE. Second, Simultaneously Non-Performing Financing and the efficiency level of Islamic commercial banks have no effect on profitability. The implication of this research is that partially NPF can be used by investors and potential investors to be used as a reference for making investment decisions.